Multiwavelength monitoring of a very active dwarf nova AX J1549.8−5416 with an unusually high duty cycle. Issue 4 (9th May 2017) - Zhang, Guobao; Gelfand, Joseph D.; Russell, David M.; Lewis, Fraser; Masetti, Nicola; Bernardini, Federico; Andruchow, Ileana; Zibecchi, L.
Abstract: We present the results of our analysis of new optical, ultraviolet (UV) and X-ray observations of a highly variable source − AX J1549.8−5416. Both the detection of several fast rise, exponential decay outbursts in the optical light curve and the lack of He ii emission lines in the optical spectra suggest AX J1549.8−5416 is a cataclysmic variable of the dwarf nova (DN) type. The multiwavelength analysis of three mini-outbursts and one normal outburst represent one of the most complete multiwavelength studies of a DN and help to refine the relationship between the X-ray, UV and optical emission in this system. We find that the UV emission is delayed with respect to the optical by 1.0–5.4 d during the rising phase of the outburst. The X-ray emission is suppressed during the peak of the optical outburst and recovers during the end of the outburst. From our analysis of archival Swift, Chandra and XMM–Newton observations of AX J1549.8−5416, we estimate this DN has a high duty cycle (∼50 per cent), suggesting a quiescent X-ray luminosity larger than 10 32  erg s −1 . We also find the X-ray and UV flux are roughly anticorrelated. Furthermore, we find that, at low X-ray fluxes, the X-ray spectrum is well described by a single temperature thermal plasma model, while at high X-ray fluxes, an isobaric cooling flow model also works. We find that the maximum temperature of the plasma in quiescence is significantly higher than that in outburst.